Sistem Informasi Manajemen Berbasis Web pada Usaha Mikro Kecil Dan Menengah (UMKM) (Studi Kasus: UMKM Sumber Jokotole, Socah, Bangkalan) - Utami, Issa Dyah; Santosa, Iwan; Annisa, Rulli; Simanjuntak, Irda Rebecca; Permatasari, Ulfi Atika; Faizah, Nur (INTEGER: Journal of Information Technology, 2019)
The Sumber Jokotole SMEs produces fish crackers with basic ingredients from fish which are fishery products from Madura. During this time, the data on the sale of products and the purchase of raw materials have not been archived, so there is some data that is lost or damaged. When the data is needed to check the number of sales, the number of purchases, looking for stock of sales and purchases, and profits, the manager of the SMEs has difficulty tracking the data. Hence the management of a good and accurate sales and financial administration system is one of the strategies that can be applied by the SMEs in dealing with competition in the ASEAN Economic Community (AEC). This research aims to aid SMEs Sumber Jokotole in managing the administration system and business processes by designing a web-based management information system (SIM) that can be accessed through computers and smartphones. The information system will provide benefits for producers, suppliers and consumers to manage business processes in the fish cracker SMEs.Keywords: Management information system, Small and medium sized enterprises, marketing